Stimulating student interest in economical specialties until the beginning of the international movement (Pedagogy of Higher and Secondary Education, 2012)
Delyk I. S. Stimulating student interest in economical specialties until the beginning of the international movement.he article grounds expediency of apply to students' motivational sphere through specific methods for stimulation of steady cognitive interest to learning foreign language.
Keywords: motivation; motive; foreign language; motivational stage; internal motivation